On Energy Harvesting Mechanism Utilizing Flexural Vibration Of A Piezoelectric Material - Susilo, Sidik (2019)
Awareness of green environment has increased the effort of scientists to seek into alternative methods to provide green energy, in which one of them is by exploiting the free energy from the environment. The way toward procuring the surrounding energy in a system and changing it into a usable electrical electrical energy is is named energy harvesting. One of the most popular methods is the utilization of piezoelectric materials to harvest the ambient vibration. This thesis presents three energy harvester systems: sound energy harvester using polyvinylidene fluoride (PVDF) piezoelectric films, vibration energy harvester using cantilevered lead zirconium titanate (PZT) and vibration energy harvester using single degree of freedom-lead zirconium titanate (SDOF-PZT) system. This study aims to evaluate and to validate experimentally the harvested electrical power for each system. Mathematical models are developed to calculate the energy harvesting performance of the each system. For the sound energy harvester using polyvinylidene fluoride (PVDF) piezoelectric films, single film with load resistance of 400 k at 97 dBA the maximum output power of 48 pW and output voltage of 5.8 mV were obtained. For the vibration energy harvester using cantilevered lead zirconium titanate (PZT) the maximum output voltage 2.04 V and output power 4.1610